KEANEKARAGAMAN JENIS POHON PENYUSUN CAGAR ALAM PANANJUNG PANGANDARAN - Darintia Amelinda Salwanafi; Denni Susanto; Vian Pradita Aniarko; Inggita Utami (Forestry Study Program University Of Mataram, 2023)
Pananjung Nature Reserve is one of the conservation areas that have unspoiled forest cover. Thus, the ecological processes in the area are still well maintained. This study aims to determine the diversity of vegetation types that make up the Pananjung Nature Reserve. Data were collected using systematic sampling with random start method with nested sampling plots. The sampling intensity used in this study was 0,5% with the number of plots as much as 58. The results showed that there are 59 tree species from 37 families. The highest tree important value index is Vitex pubescens with a value of 29,96%. Meanwhile, the diversity index value (H') of the trees that make up the Pananjung Nature Reserve is 3,55. Based on this value, the diversity index is in high category.Â